Clinical and Immunological Features of Allergen-Specific Immunotherapy for Bronchial Asthma in Children - S.M. Nedelska; N.M. Taran (Zaslavsky O.Yu., 2014)
The article presents the results of a study on the clinical and immunological course of bronchial asthma, depending on its phenotype and duration of specific immunotherapy. It is shown that allergen-specific immunotherapy with mite, epidermal and pollen allergens clinically and immunologically is a highly effective method of bronchial asthma treatment in children; immunotherapy with mite allergens has greater clinical efficacy than pollen and epidermal one; in terms of immunological parameters, allergen-specific immunotherapy with epidermal allergens is more effective than mite and pollen one, which can be explained by specific prevalence of epidermal animal allergens in the environment; use of immunotherapy in the treatment of bronchial asthma enables immune rehabilitation of children having various kinds of sensitization.